The Influence of Service Quality and Price on Customer Satisfaction at Roti Bakar 88 Kemayoran, Jakarta - Dino Gustaf Leonandri; Rina Fitriana (Institute of Computer Science (IOCS), 2021)
This study aims to find out the influence of service quality and price on the customers’ satisfaction at Roti Bakar 88 Kebayoran, Jakarta. This research is a quantitative study using descriptive quantitative methods. Data collection was carried out through questionnaires distributed to 150 respondents. Data analysis methods used are validity test, reliability test, descriptive statistical test, determinant coefficient test, multiple linear regression test, T test, and F test. Based on the research results, it shows that service quality has a significant and positive influence on customers’ satisfaction with a magnitude of 0.291, which means that if the service quality increases, the level of customers’ satisfaction will be higher. Price has a significant and positive effect no customers’ satisfaction with magnitude of 0.419, which means that if the price increases, the level of customers satisfaction will decrease.